Noninvasive monitoring of cerebrovascular autoregulation response to resistance exercises - Petkus, V.; Kalasauskiene, A.; Ragauskas, A.; Chomskis, R.; Krutulyte, G.; Kalasauskas, L. (Medicina, 2012)
Background and Objective. A novel noninvasive monitor is presented by demonstrating its capabilities to perform the real-time estimation of dynamics in cerebrovascular autoregulation in athletes during their training. The aim was to explore the characteristics of human cerebrovascular autoregulation by performing the monitoring of cerebrovascular autoregulation responses to resistance exercises in healthy volunteer athletes.